2000
DOI: 10.1292/jvms.62.711
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Efficacious Dosage of Flecainide Acetate for Treating Equine Atrial Fibrillation.

Abstract: ABSTRACT. To determine a safe and efficacious dose of flecainide acetate for treating equine atrial fibrillation (Af), the safe dosage level was determined by injecting 1, 2, or 3 mg/kg i.v. of 1% flecainide acetate solution at a rate of 0.2 mg/kg/min to five clinically healthy horses. Clinical signs and the ECG were monitored (HR, PR, QRS, and QT intervals) and blood was taken to measure the plasma flecainide concentration pre-and post-administration. No abnormal signs were observed in the 1-or 2-mg/kg groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 13 publications
7
47
3
Order By: Relevance
“…To obtain a more specific ventricular repolarization time, JTc intervals were calculated, and in contrast to what has been documented in humans,20 flecainide temporarily prolonged JTc in horses. The present study however did not identify any potentially dangerous ventricular arrhythmias, which is in agreement with other studies 1, 3. However, 3 cases of flecainide‐induced wide QRS‐tachycardia have been reported in horses2, 4 of which 1 episode led to ventricular fibrillation and sudden cardiac death.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To obtain a more specific ventricular repolarization time, JTc intervals were calculated, and in contrast to what has been documented in humans,20 flecainide temporarily prolonged JTc in horses. The present study however did not identify any potentially dangerous ventricular arrhythmias, which is in agreement with other studies 1, 3. However, 3 cases of flecainide‐induced wide QRS‐tachycardia have been reported in horses2, 4 of which 1 episode led to ventricular fibrillation and sudden cardiac death.…”
Section: Discussionsupporting
confidence: 93%
“…To investigate whether flecainide affected ventricular repolarization, we evaluated changes in QTc and JTc intervals. In a previous study of horses, no flecainide‐induced changes in QT intervals were reported 1. In our study, QTc was significantly prolonged between 6 and 25 minutes after flecainide infusion was started.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…We have shown in a previous study that flecainide given intravenously is a safe and effective agent for treating equine atrial fibrillation [8]. For the conversion of atrial fibrillation to sinus rhythm, a total dose of 1.4 ± 0.63 mg/kg flecainide was required intravenously, the time to conversion was 7.0 ± 3.15 min and the effective plasma concentration was 1,303 ± 566 ng/ml [8]. However, that is the only report on the use of flecainide for treating atrial fibrillation in horses, thus, nothing is known about its behavior following oral administration or its pharmacokinetics in horses.…”
mentioning
confidence: 98%
“…It is particularly effective as a drug for converting paroxysmal atrial fibrillation to sinus rhythm [5,7,10,11]. We have shown in a previous study that flecainide given intravenously is a safe and effective agent for treating equine atrial fibrillation [8]. For the conversion of atrial fibrillation to sinus rhythm, a total dose of 1.4 ± 0.63 mg/kg flecainide was required intravenously, the time to conversion was 7.0 ± 3.15 min and the effective plasma concentration was 1,303 ± 566 ng/ml [8].…”
mentioning
confidence: 99%